The left ventricular remodeling assessment by cardiac magnetic resonance in chronic aortic regurgitation; implications for outcome. (14th October 2021) - Hashimoto, G; Sarano, M; Sato, H; Lopes, B; Fukui, M; Stanberry, L; Cheng, V; Garcia, S; Goessl, M; Sorajja, P; Bapat, V; Lesser, J; et al.
Abstract: Background: Chronic aortic regurgitation (AR) causes left ventricular (LV) volume overload resulting in progressive LV remodeling, which negatively affect clinical outcome. Clinical Guidelines recommend assessment of LV remodeling by echocardiography, but little is known about comparative remodeling quantification by cardiac magnetic resonance (CMR) and association with outcomes. Purpose: To assess LV remodeling in AR by CMR, compared with echocardiographic measures and determine its impact on clinical outcome. Methods: Patients with native, ≥moderate, chronic AR by echocardiography who underwent CMR exam within 90 days of diagnosis from January 2012 to February 2020 were enrolled. The endpoint was a composite of death, heart failure hospitalization, and heart failure symptom exacerbation during follow-up. Results: The 178 patients included had median age (IQR) of 58 years (44–69), and most (88%, n=158) presented with no or minimal symptoms (NYHA class I/II). At diagnosis symptomatic vs. no/minimal symptoms patients presented with much more advanced LV remodeling by CMR (EDVI 133 [83–151] vs. 96 [80–123] p=0.024, ESVI 66 [46–85] vs. 42 [30–58], P=0.001) while echocardiography showed limited differences (EDVI 76 [57–93] vs. 65 [54–87] p=0.507, ESVI 38 [30–58] vs. 27 [20–42], p=0.072). During follow-up (3.3 years [1.6–5.8]), aortic valve replacement (AVR) was performed in 49 patients. In patients with no/minimal symptoms, the composite endpoint occurred in 54 (34%) patients including eight deaths and 30 heart failure hospitalizations. Patients with LV end-systolic volume index (LVESVi) >45 ml/m 2 by CMR had higher likelihood for composite endpoint (Panel A) confirmed in multivariate models, adjusting for age, sex, AVR (time-dependent), EuroSCORE2, and LV End-systolic-dimension-index (LVESDi) >25 mm/2, with adjusted hazard ratio 1.84 [1.02–3.33], p<0.044 (Panel B). LVESVi by CMR was at least as powerful in determining clinical outcomes as guideline-recommended Doppler-Echocardiographic variables. Conclusion: Assessment of LV remodeling by CMR in patients with clinically significant AR is feasible in routine clinical practice, detects with high sensitivity LV remodeling associated with development of HF symptoms and is independently predictive of clinical outcome. Hence, CMR provides a powerful tool for evaluation and risk stratification of patients with AR. Funding Acknowledgement: Type of funding sources: None.